A COMPARISON OF THE TRADITIONAL (WESTERN STYLE) BANK AND ISLAMIC BANK MODELS - Adnan, Muhammad A; Gaffikin, M.J.R (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 1998)
There has been a remarkable increase in the number Islamic banks and Islamic Financial Institution since the 1970s. There are about a hundred Islamic Banks and Financial Institutions currently in the world. It is useful and interesting to know how Islamic banks differ from the Western (Traditional) style bank?This paper surveys the differences between the twostyle of bank. A comparison is made of the origin of each style of bank. their development, the types of products and services they offer: their organization and their financial statements.The paper concludes that the basic difference is in the treatment of interest. But this in tum generates some other differences. Interestingly, in the sense of accounting concepts and practices, it seems that both styles are not significantly different.However. a close examination of this seems to be interesting and is the focus of study, because each style of bank has developed with different perspective.